2023
DOI: 10.3389/fnut.2023.1114758
|View full text |Cite
|
Sign up to set email alerts
|

Earlier anti-TNF therapy reduces the risk of malnutrition associated with alterations in body composition in patients with Crohn’s disease

Abstract: BackgroundAnti-TNF therapy has been found to exert an influence on long-term nutritional status and even reverse malnutrition in patients with Crohn’s disease.Aimsto observe the effect of anti-TNF therapy on nutritional status in patients with Crohn’s disease, investigate the correlation between the timing of anti-TNF therapy and the human body composition and examine independent body composition factors for predicting malnutrition in these patients.MethodsThis was a retrospective study of 115 patients with Cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…In this study, it was found that the longer the time of use of IFX, the higher the BMI and waist circumference. Despite the beneficial effect on the recovery of nutritional status, which is already observed from the beginning of the IFX induction protocol until the maintenance 8,9 . Santos et al 7 (2017) found significant increase in BMI (22.9 ± 3.2 versus 25 ± 3.8 kg/m 2 ; p = 0.005), waist circumference (88.1 ± 6.7 versus 93.9 ± 7.7 cm; p = 0.002) and body fat index (5.5 ± 2.3 versus 6.8 ± 2.3 kg/m 2 ; p = 0.000) after 6 months of treatment with anti-TNF-α therapy.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In this study, it was found that the longer the time of use of IFX, the higher the BMI and waist circumference. Despite the beneficial effect on the recovery of nutritional status, which is already observed from the beginning of the IFX induction protocol until the maintenance 8,9 . Santos et al 7 (2017) found significant increase in BMI (22.9 ± 3.2 versus 25 ± 3.8 kg/m 2 ; p = 0.005), waist circumference (88.1 ± 6.7 versus 93.9 ± 7.7 cm; p = 0.002) and body fat index (5.5 ± 2.3 versus 6.8 ± 2.3 kg/m 2 ; p = 0.000) after 6 months of treatment with anti-TNF-α therapy.…”
Section: Discussionmentioning
confidence: 98%
“…When compared with conventional therapy, IFX treatment promotes sudden and prolonged regulation of inflammation, stimulating mucosal healing. In this way, it promotes the recovery of nutritional status with weight gain and increase in strength and muscle mass [6][7][8][9][10] . However, after six months of treatment, patients have a significant increase in abdominal obesity and body fat 7 .…”
Section: Introductionmentioning
confidence: 99%
“…100 In another retrospective study of patients with CD, the median SMI values were significantly higher in those who were on Anti TNF therapy than those who were not (P = 0.01). 113 In a longitudinal cohort study on patients initiated on anti-TNF therapy, after a median follow-up of 5 years, there was a significant improvement in all the muscle parameters (skeletal muscle index; P < 0.001, skeletal muscle area; P < 0.001, psoas muscle area, P = 0.03) measured on CT. 114 In another retrospective study where the prevalence of myopenia was studied in patients who underwent surgery for IBD (surgical cohort) and who were initiated on biologics (medical cohort), after a follow-up period of 1 year, the prevalence of myopenia was higher in the surgical cohort when compared with the medical cohort (32% vs. 16%, P < 0.02). 115 The impact of biological use in IBD was also prospectively studied in patients with CD, where the assessment of muscle strength and mass was done at baseline and 25 weeks later and found that there was a significant improvement in both muscle strength (P = 0.002) and muscle mass (P = 0.01), and this gain was independent of steroid usage.…”
Section: Impact On Managementmentioning
confidence: 99%